Indigenous patterns of music discovery: Khwe Bushmen and hip-hop in Platfontein, South Africa. (2nd July 2016) - Bodunrin, Itunu
ABSTRACT: Hip-hop has become a platform for young Khwe Bushmen to negotiate restrictive urban spaces following the tribe's resettlement near the city of Kimberley in the Northern Cape province of South Africa. Previous studies on music discovery tend to ignore the plight of indigenous and rural youth who struggle to keep up with the pace of global trends. Using qualitative data obtained through participatory observation, interviews, and focus group discussions, I argue that class remains a significant factor in the discovery of music. In many African indigenous communities, a few persons with higher socioeconomic status play a significant role in the acculturation and distribution of digital music and music cultures.